Persepsi Mahasiswi Terhadap Poligami Dalam Perspektif Kesetaraan Gender Sebagai Konstruksi Sosial: Studi Kritis Tanpa Dasar Justifikasi Normatif Di Jurusan PPKn Unimed - Natasya Windi Aqilla; Parlaungan Gabriel Siahaan; Desvita Dwi Herawati; Kevin Rahmat Immanuel (JURNAL MANAJEMEN PENDIDIKAN, 2026)
FEMALE STUDENTS’ PERCEPTIONS OF POLYGAMY FROM A GENDER EQUALITY PERSPECTIVE AS A SOCIAL CONSTRUCTION: A CRITICAL STUDY WITHOUT NORMATIVE JUSTIFICATION IN THE CIVIC EDUCATION (PPKn) DEPARTMENT AT UNIVERSITAS NEGERI MEDAN (UNIMED) Polygamy constitutes a persistent subject of scholarly debate as a social phenomenon, particularly when examined through the lens of gender equality. Normatively, this practice is subject to regulation by statutory law and religious doctrines, predicated on the principle of fairness. However, empirical realities frequently demonstrate the emergence of unequal power dynamics between men and women. This divergence engenders a spectrum of perceptions within the community, including among female university students, who serve as intellectual agents in cultivating critical perspectives on social issues. The perceptions of female students regarding polygamy are shaped by multidimensional factors, including their conceptual understanding of gender, educational trajectories, and internalized value systems. Accordingly, systematic examination of female students' views on polygamy, independent of normative justification, is warranted to ascertain attitudinal predispositions and the variables influencing these perceptions. This study employs a qualitative approach using a phenomenological method through in-depth interviews. The research was conducted in the Civic Education (PPKn) Department, Faculty of Social Sciences, Universitas Negeri Medan (UNIMED). The subjects of this study are 20 female students from the 2024 and 2025 cohorts, selected using purposive sampling (10 students from each cohort). Data were collected through in-depth interviews and observation designed based on indicators of perceptions of polygamy and gender equality as social construction. The collected data were analyzed using thematic analysis to identify general trends in informants' perceptions, as well as to examine the relationship between gender understanding and attitudes toward polygamy. The findings reveal that female students of PPKn UNIMED from the 2024 and 2025 cohorts predominantly reject polygamy when examined from the perspective of gender equality as a social construction. Mean scores of 3.66 for the perception dimension and 3.77 for the attitudinal dimension (on a 5.00 scale) indicate a high tendency toward rejection. A total of 95% of informants (19 out of 20) expressed rejection, with no informants found to support polygamy. Gender education was found to exert a significant influence on the formation of students' critical perceptions, as reflected in a mean score of 4.31 for the gender education influence dimension. Students demonstrated the ability to identify the gap between das sollen and das sein in polygamy practice, and perceived polygamy as an expression of hegemonic masculinity that reinforces the subordination of women.